Contextual ITSM Adoption Across Educational Levels: A University and a Secondary School in Jakarta - Marcel, Marcel; Azhar, Nur Chalik (Journal of Information System and Informatics, 2025)
This research investigates contextual ITSM adaptation across educational levels through a comparative case study of a university and secondary school in Jakarta. Using qualitative methodology with interviews, observations, and document analysis, we examined implementation patterns at University X (5,000 students, 12 IT staff) and SMA Y (450 students, 2 IT staff). Results show universities achieved semi-formal ITSM maturity levels 2-3 while secondary schools operated at pragmatic levels 1-2, reflecting resource disparities where universities allocated 4% versus 1.5% of operational budgets to IT services. Key findings reveal persistent perception gaps where academic staff predominantly view IT as "repair function" rather than strategic service, with most service requests still submitted through informal channels instead of standardized procedures. Three primary implementation challenges emerged: resource limitations, structural complexity, and cultural resistance. Based on these findings, we propose a phased transformation model (Stabilization, Standardization, Development) accommodating "layered maturity" - allowing institutions to operate at different maturity levels across ITSM domains rather than uniform advancement. This research contributes a contextual ITSM implementation framework bridging industry standards with educational realities, providing practical guidance for institutions balancing digital transformation aspirations with resource constraints, particularly relevant for developing countries facing similar educational technology challenges.